2022
DOI: 10.1186/s13293-022-00429-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal insulin sensitivity in late pregnancy in women carrying a male fetus: a cohort study

Abstract: Background It has been suggested that fetal sex may be able to modify maternal metabolism and physiology during pregnancy. Recently pregnant women carrying a male fetus were reported to be more insulin sensitive than those carrying females, although related evidence is inconsistent. Methods In this study we administered a 75 g oral glucose tolerance test at around week 28 of pregnancy in 813 pregnant women from a contemporary birth cohort (the Camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, in our study, women who developed GDM exhibited a 27% greater incidence of delivering female children than male ones. Recent findings have demonstrated that fetal sex may exert a role on maternal insulin sensitivity [ 52 ]. In GDM, the placenta is affected, and different gene expression takes place, with fetal sex playing an important role [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in our study, women who developed GDM exhibited a 27% greater incidence of delivering female children than male ones. Recent findings have demonstrated that fetal sex may exert a role on maternal insulin sensitivity [ 52 ]. In GDM, the placenta is affected, and different gene expression takes place, with fetal sex playing an important role [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GDM and fetal sex, Hooks et al [ 57 ] found that in women with GDM, having a male fetus raises the probability of preterm birth [ 55 ], while Seghieri et al [ 58 ] found that having a male fetus raises the likelihood of GDM, and in pregnancies with a female fetus, maternal obesity before gestation increases the probability of GDM. Another recent study found that having a male fetus is associated with higher insulin sensitivity [ 52 ]. Moreover, Mando et al explored the potential effect of GWG on fetal/placental ratio in overweight with different fetal gender and found different placenta adaptation depending on fetal sex, with substantial alterations merely in female fetuses [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although current antenatal evaluation of GDM risk in pregnant women only involves the assessment of maternal characteristics, it is likely that also fetal, paternal, and/or placental factors affect its development and contribute to the observed heterogeneity in terms of obstetric and fetal outcomes [21]. The role of fetoplacental factors is suggested by epidemiological studies showing that GDM risk and/or maternal glycemia are affected by, e.g., fetal sex [73], multiple pregnancies [74], paternal age [75], and paternal ethnicity [76]. Moreover, a recent meta-analysis reported that GDM reoccurs only in approximately half of subsequent pregnancies [77]-less than what could be expected if GDM were only a sign of deranged glucose metabolism in the mother [21].…”
Section: Fetal Paternal and Placental Genetic Risk Factors Of Gdmmentioning
confidence: 99%
“…Males and females show differential expression of genes involved in several different functions in the placenta, providing a potential mechanism by which differential growth strategies could be achieved [11][12][13][14][15][16][17][18][19]. These could, in turn, contribute to sex differences in fetal oxygen extraction and maternal glucose metabolism [20,21].…”
Section: Introductionmentioning
confidence: 99%